A Study on Making Rigid Polyurethane Foams from Vietnam Rubber Seed Oil-Based Polyol by Using Water as a Single Blowing Agent - Nguyen Thi Thuy; Pham Ngoc Lan (International Journal of Polymer Science, 2021)
In this work, for making rigid polyurethane foams, only water was used to serve as a blowing agent. Vietnam rubber seed oil-based polyol was also used. Following our previous research results, water content was fixed at 4 wt.% and glycerol content at 3 wt.%, as compared to biopolyol. The effect of the NCO/OH ratio, main catalyst (dibutyltin dilaurate), cocatalyst (triethylamine), and surfactant content as well as the surfactants on performances of foams was investigated through compressive strength, density, cell size, and size distribution. A suitable formulation for making foam by using biopolyol made from rubber seed oil was established. In parallel with it, foam based on commercial polyol derived from petroleum was also manufactured. The characteristics of the foaming process were assessed. The mechanical properties, thermal behavior, water absorption, and dimensional stability of foams were evaluated. The cellular morphology study shows that the cells of foam based on biopolyol were closed and rather uniform; however, cell size was 3% bigger and cell walls were also a bit thicker. The results showed that the properties of foam based on biopolyol were similar to those of petrofoams. This result may open a possibility to replace petropolyol with renewable biopolyol in foam fabrication.